Skrining Anemia Remaja Putri di Pondok Pesantren Asshohwah Al-Islamiyah Desa Beleka Gerung Lombok Barat - Turmuzi Turmuzi; Fariani Syahrul; Lalu Madahan (Universitas Malahayati Lampung, 2023)
ABSTRACT Anemia is a condition with hemoglobin levels that are lower than normal in adolescent girls, namely 12 g/dl. The prevalence of problematic anemia in adolescent girls shows 15%. The impact of anemia on adolescent girls which causes growth disorders, easy infection, reduced body fitness, decreased enthusiasm for learning and achievement, reduced physical abilities in preparation for becoming prospective mothers poses a risk to the health of the mother and the baby she is carrying. Carrying out anemia screening in adolescent girls to determine the clinical picture, namely weak, tired, lethargic, tired, inattentive and other clinical features using Hb Sahli at the Asshohwah Al-Islamiyah Islamic Boarding School, Beleka Gerung Village, West Lombok. Using descriptive observational. The sample in the study was 107 young women at the Asshohwah Al-Islamiyah Islamic Boarding School with inclusion criteria based on clinical symptoms of anemia. By using validity analysis to determine sensitivity, specificity, Positive Predictive Value (PPV) and Negative Predictive Value (NPV). Of the 107 young women who were examined for anemia, descriptive clinical symptoms were known, namely 19.63% had weak symptoms. 51.40% tired, 17.76% lethargic, 16.82% tired, 46.73% inattentive, 15.89% dizzy and 64.49% dizzy. Validity analysis for the highest sensitivity to dizziness symptoms 75.68 %, specificity for symptoms was 84.29%, the highest Positive Predictive Value (PPV) for symptoms of weakness was 47.61% and the highest Negative Predictive Value (NPV) for symptoms of dizziness was 84.29%. The prevalence of anemia in adolescent girls at the Asshohwah Al-Islamiyah Islamic Boarding School in Beleka Village, West Lombok is 27.10%. The health center carries out regular screening, provides counseling, gets used to a healthy lifestyle, and provides blood supplement tablets (Fe) to anemic adolescent girls. . Keywords: Screening, Validity, Anemia in Adolescent Girls ABSTRAK Anemia adalah suatu keadaan dengan kadar hemoglobin yang lebih rendah dari normal pada remaja putri adalah 12 g/dl Prevalensi anemia bermasalah pada remaja putri menunjukkan 15%. Dampak anemia pada remaja putri yang menyebabkan gangguan masa pertumbuhan, mudah terinfeksi, kebugaran tubuh berkurang, semangat belajar dan prestasi menurun, menurunkan kemampuan fisik persiapan menjadi calon ibu berisiko terhadap kesehatan ibu dan bayi yang dikandungnya. Melakukan skrining anemia pada remaja putri untuk mengetahui gambaran klinis yaitu lemah,letih,lesu,Lelah,lalai dan klinis lainnya menggunakan Hb Sahli di Pondok Pesantren Asshohwah Al-Islamiyah Desa Beleka Gerung Lombok Barat. Menggunakan observasional deskriptif. Sampel dalam penelitian adalah remaja putri di Pondok Pesantren Asshohwah Al-Islamiyah berjumlah 107 orang dengan kriteria inklusi berdasarkan gejala klinis anemia. Dengan menggunakan analisis validitas untuk mengetahui sensitivitas, spesifisitas, Positif Predictive Value (PPV) dan Negatif Prdicive Value (NPV). Dari 107 Remaja Putri yang diperiksa anemia deskritf gejala klinis diketahui yaitu 19,63% gelaja lemah. 51,40% lelah, 17,76%, lesu, 16,82% letih, 46,73% lalai, 15,89% berkunang-kunang dan 64,49% pusing .Analisi Validitas untuk sensitifitas tertinggi pada gejala pusing 75,68%, spesifisitas pada gejala 84,29%, Positif Predictive Value (PPV) tertinggi pada gejala lemah sebesar 47,61% dan Negative Predictive Value (NPV) tertinggi pada gejala Pusing 84,29%. Prevalensi anemia pada remaja putri di di Pondok Pesantren Asshohwah Al-Islamiyah Desa Beleka Lombok Barat adalah 27,10% Puskesmas melakukan skrining secara berkala,memberikan penyuluhan,,membiasakan pola hidup,sehat,dan pemberikan tablet tambah darah (Fe) pada remaja putri anemia. Kata Kunci: Skrining,Validitas,Anemia Remaja Putri